Five new species of the genus Ernolatia Walker, 1862 (Lepidoptera: Bombycidae) from islands of Malesia - Zolotuhin, Vadim V.; Dolgunov, Vladislav A. (Zootaxa, 2018)
Five new species of the genus Ernolatia Walker, 1862 are described from the islands of Malesia. They are E. adrasteia sp. nov. (type locality: Philippinen, Negros occ., Mt. Kanlaon, 600-800 m, W-Route via Mambucal), E. invicema sp. nov. (type locality: S. Sulawesi, Puncak, Palopo, 2°55’S, 120°05’E), E. callirhoe sp. nov. (type locality: S. Sulawesi, Mt. Sampuraga, 2°10’S, 120°45’E), E. fumidiflora sp. nov. (type locality: Indonesia, N. Tengg. Timur, Flores, 9 km S Ruteng Golo Luseng) and E. doris sp. nov. (type locality: Indonesia, Sumba (W), Prov. Nusa Tenggara Barat, Gunung (Mt) Areas). The holotypes of all taxa are deposited in the coll. of entomological Museum Witt (which will be attributed to the Zoologische Staatssammlung, Munich). Their habitus, as well as available genitalia, are illustrated.